Sosialisasi Sistem Pencatatan Keuangan Secara Manual dan Digital Pada Ukm di Cisarua – Bogor - Hendra Candra; Haria Saputri; Patria Adiguna; Fisy Amalia; Adhy Firdaus; Muhammad Ramdhan; Qona’ah Adiahita; Zulfikar Hidayat; Ainun Naim; Wahid Hasyim; M.Khairul Umam; Dine Eka Putri (Universitas Muhammadiyah Manado, 2020)
The impact of Covid-19 Virus is very significant for Indonesia economic, especially for small traders or generally called Small and Medium Enterprises (SMEs). In connection with the situation of the Covid-19 pandemic which is more better, the tourism in Cisarua Bogor has also begun to be visited by visitors so that the SMEs have also begun to actively trade again. Along with this, the community service is carried out with the aim of providing socialization and training to SMEs regarding the financial transaction recording system in their businesses. The methods used are socialization, counseling, discussion, interviews and training to SMEs around Cibereum Village RT.001 / RW.006, Cisarua District, Bogor Regency. This activity lasted for 2 (two) weeks starting from preparation and planning, while the implementation of the activity is 2 (two) days, and the community service Team is 17 lecturers of STIE Ganesha Jakarta were followed by 10 lecturers of Management and 7 lecturers of Accounting. The results obtained from counseling and discussion is SMEs understand if the importance of financial recording in their business. While the results of training and mentoring, the SMEs feel more clearly and on path about the entry and exit of funds from their business results and the application is also quite easy to understand. The advice that can be given is that SME traders who have not yet recorded should immediately start implementing financial records even though with simple record and for SME traders who already have records but not yet neat, should start tidying up the financia lrecord transactions according to what has been explained above.